Neighbors follow early adopters under stress: Panel data analysis of submergence-tolerant rice in northern Bangladesh - Yamano, Takashi; Malabayabas, Maria Luz; Habib, Md. Ashraful; Das, Subrata Kumar (Wiley, 2018)
The benefits of a stress‐tolerant crop become visible under the stresses that the crop is tolerant against. We investigate the adoption of submergence‐tolerant rice in northern Bangladesh by using panel data of 461 households, interviewed in 2013 and 2015. The sample households were randomly selected in 31 villages where submergence‐tolerant rice seeds were given to a small number of farmers in each village. The results from the household fixed‐effects model indicate that submergence in the previous year increased the adoption of submergence‐tolerant rice. The adoption impact was larger among farmers who were neighbors of early seed recipients. Our results suggest that being neighbors of early seed recipients may have helped the neighboring farmers observe the benefits of the submergence‐tolerant rice under submergence. The results indicate the importance of the information flow from early recipients to neighboring farmers.